A new species of Kniphofia (Asphodelaceae) from Nyungwe National Park, Rwanda - Fischer, Eberhard; Ackermann, Markus (Phytotaxa, 2019)
A new species, Kniphofia vandeweghei, is described and illustrated, and the differences with K. princeae, K. goetzei and K. paludosa are discussed. Distribution maps for K. vandeweghei and K. princeae are provided. Kniphofia bequaertii, sometimes regarded as a synonym of K. grantii, is considered to be a good species, and identification characters and distribution information are given. An identification key for all known Kniphofia species from Rwanda is provided.